Comprehensive analysis of prohibited substances and methods in sports: Unveiling trends, pharmacokinetics, and WADA evolution - Oleksak, Patrik; Nepovimova, Eugenie; Valko, Marian; Alwasel, Saleh; Alomar, Suliman; Kuca, Kamil (Environmental toxicology and pharmacology, 2024)
This review systematically compiles sports-related drugs, substances, and methodologies based on the most frequently detected findings from prohibited lists published annually by the World Anti-Doping Agency (WADA) between 2003 and 2021. Aligned with structure of the 2023 prohibited list, it covers all proscribed items and details the pharmacokinetics and pharmacodynamics of five representatives from each section. Notably, it explores significant metabolites and metabolic pathways associated with these substances. Adverse analytical findings are summarized in tables for clarity, and the prevalence is visually represented through charts. The review includes a concise historical overview of doping and WADA's role, examining modifications in the prohibited list for an understanding of evolving anti-doping measures.
Keywords: doping ve sportu; lidé; Performance-Enhancing Substances; Substance Abuse Detection; odhalování abúzu drog; Humans; látky zvyšující výkon; Doping in Sports